The National SOM Survey Cumulative Dataset 1986-2021 - SOM Institute, University of Gothenburg (University of Gothenburg, 2023)
In order to identify how the evolution of society affects Swedes’ attitudes and behaviour, the SOM Institute started its National SOM study in 1986. National SOM addresses three areas - society, opinions and mass media - and consists of a large number of questions related to politics, society, media and social background, but their areas of focus differ. Every year, the questionnaires are complemented with questions related to current events. Data is collected through postal questionnaires with an option to respond to the survey online, and each survey is conducted under conditions as identical as possible to make the results from the different years comparable.

The SOM Institute Cumulative Dataset contains data from the National SOM surveys from 1986. The data contains a selection of questions frequently asked over the years, focusing on time series. A general rule is that questions should have been asked at least four times.

The main purpose is to establish time series that enable researchers to analyse how various changes in society affect people's attitudes and behaviour.

SOM-institutet vid Göteborgs universitet genomför varje höst sedan 1986 en nationell frågeundersökning - Den nationella SOM-undersökningen - i syfte att kartlägga den svenska allmänhetens vanor och attityder på temat samhälle, politik och medier (SOM står för Samhälle Opinion Medier). Data samlas in via postala enkäter där möjlighet ges att svara på webben, och varje undersökning genomförs under så identiska förutsättningar som möjligt för att resultaten från de olika åren ska vara jämförbara.

Den nationella SOM-undersökningens kumulativa dataset innehåller data från den nationella SOM-undersökningen från och med 1986. De frågor som inkluderas i superfilen är ett urval av de som ställts varje år i Den nationella SOM-undersökningen, med fokus på tidsserier (i regel med fler än fyra mätpunkter).

Huvudsyftet är att etablera tidsserier som gör det möjligt att analysera hur olika samhällsförändringar påverkar människors attityder och beteenden.
Den nationella SOM-undersökningens kumulativa dataset 1986-2021
Super-Riks-SOM
Keywords: housing; boende; mass media; massmedia; population migration; migration; occupations; yrken; participation; deltagande; environment; miljö; mass media exposure; massmediaexponering; health; hälsa; interpersonal relations; mellanmänsklig relation; religious attendance; religiöst deltagande; trust; förtroende; european union; europeiska unionen; political interest; politiskt intresse; local government services; kommunal service; nuclear energy; kärnkraft; membership; medlemskap; trade union membership; medlemskap i fackförening; medical care; sjukvård; public services; offentlig service; immigration policy; invandringspolitik; news; nyheter; foreign policy; utrikespolitik; privatization; privatisering; taxation; beskattning; ideologies; ideologi; television viewing; tv-tittande; research; forskning; religious beliefs; religiös tro; religious affiliation; religiös tillhörighet; democracy; demokrati; defence and state security policy; försvars- och säkerhetspolitik; internal politics; inrikespolitik; labour market; arbetsmarknad; political parties; politiska partier; international cooperation; internationellt samarbete; climate; klimat; internet use; internetanvändning; political leaders; politiska ledare; religious behaviour; religiöst beteende; citizen participation; medborgardeltagande; households; hushåll; libraries; bibliotek; leisure time activities; fritidsaktiviteter; mass media use; mediaanvändning; interest (cognitive processes); intresse (kognitiva processer); renewable energy; förnybar energi; values; värderingar; refugees; flyktingar; political issues; politiska frågor; energy efficiency; energisparande